Are Prices Countercyclical? - Prasad, Eswar; Chadha, Bankim (Washington, D.C. : International Monetary Fund, 1992)
This paper examines the comovement of prices with the cyclical component of output. It argues that determining the cyclical behavior of prices by applying the same stationarity-inducing transformation to the levels of both output and prices, and examining the correlations of the resulting series, can be misleading. A more appropriate procedure is to examine the correlations between the rate of inflation and the level of the cyclical component of output. In post-war U.S. data the correlations between similarly transformed price and output data are consistently and often strongly negative, as reported recently by a number of authors as evidence of countercyclical price behavior. The rate of inflation, however, is consistently and usually strongly positively correlated with various measures of the cyclical component of output.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Demand; Aggregate Price Level; Price Movement; Rate Of Inflation; WP; United States